Efektivitas Teh Kompos Berbahan Dasar Berbeda pada Pertumbuhan dan Produksi Rumput Benggala (Panicum maximum) - Dedi Tahoni; Oktovianus R. Nahak; Polikarpia W. Bani (JAS, 2019)
This research has been carried out in the experimental garden owned by the Faculty of Agriculture of the University of Timor, Sasi Village, Kefamenanu City District, Timor Tengah Utara Regency for one planting period (45) days from November 2018 to January 2019. The purpose of this study is to determine the effectiveness Compost based tea is different from the growth and production of Bengal grass (Panicum maximum). This study uses the experimental method, using a completely randomized design (CRD) with 4 treatments 4 replications so that there are 16 units of experimental units. The treatments tested are as follows: R0: Without Compost Tea. R1: Guano-based Compost Tea. R2: Compost Tea Made from Cow's Stool. R3: Compost Tea Made from Chicken Exkreta. Variables observed were plant height, number of leaves, number of tillers, fresh weight of plants, dry weight of plants. The results showed that the effect of the treatment of different compost-based tea produced the best plant height in the treatment of chicken exkreta compost based on the treatment R3 by 108, 12 cm, the highest number of tillers on R3 treatment with 3.85 tillers of chicken exkreta. The highest number of leaves was R3 treatment with 7 compost based chicken compost tea, 21 leaves, the lowest dry weight in R3 treatment with compost tea made from chicken exkreta as much as 190, 499%, highest fresh weight on R3 treatment with compost tea chicken exkreta base as much as 950.00 g. However, statistically it was shown that the treatment of different compost-based compost teas at the same level produced growth and production that were the same or not significantly different (P> 0.05) for all variebel observations (Plant Height, Number of Leaves, Number of tillers, Fresh Weight and Dry Weight) It was concluded that the administration of guano-based compost tea, cow feces and chicken exkreta produced the same growth and production value because the nutrients available in the given compost tea were relatively the same.